On sequence convergence in (3,j)-metric spaces, j∈{1,2} - Donco Dimovski, Pavel Dimovski, Tomi Dimovski (Union of Mathematicians of Macedonia, 2024)
In this article, we show that a convergent sequence in (3, 2)-metric spaces has a unique limit. We give several examples in (3, 1, ρ)-metric spaces and (3, 1)-metric spaces in which a convergent sequence has more than one limit. We obtain sufficient conditions for a sequence in (3, 1)-metric space to have a unique limit.
Keywords: (3, 1, ρ)-metric space, (3, 2, ρ)-metric space, (3, 1)-metric space, (3, 2)-metric space